2014
DOI: 10.7747/jfs.2014.30.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Above Ground Carbon Stock Through Palm Tree in the Homegarden of Sylhet City in Bangladesh

Abstract: An explanatory survey was conducted to assess the contribution of palm species in carbon sequestration in the homegarden of the Sylhet Metropolitan City Corporation of Bangladesh. Assessment was done by means of two stage random sampling. A total of 10 housing area were selected randomly for the study and 4 common palm tree species were found abundantly.From the observations abundance of palm trees [Areca catechu (175/housing area), Cocos nucifera (145/housing area), Borassus flabellifer (124/housing area) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…It is a serious environmental issue affecting humans through its consequence on temperature increase, sea-level rise due to melting of glaciers and sea ice, changes in the location of appropriate habitat for plants and animals, amongst other. Mitigation of global warming is a major environmental challenge today [2]. Thus reducing global warming entails reducing the atmospheric concentrations of GHGs, particularly CO2.…”
Section: Introductionmentioning
confidence: 99%
“…It is a serious environmental issue affecting humans through its consequence on temperature increase, sea-level rise due to melting of glaciers and sea ice, changes in the location of appropriate habitat for plants and animals, amongst other. Mitigation of global warming is a major environmental challenge today [2]. Thus reducing global warming entails reducing the atmospheric concentrations of GHGs, particularly CO2.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings add new knowledge to the current global discussions of the role of small-scale forests and trees outside the forests in combating global warming. Consistent with the methods in previous studies on other types of small forests and other areas worldwide [10,12,14,17], we quantified the carbon sequestration in small plots of private forests and the trees outside of the forest, which are neglected and largely lacking in the current international literature. The total amount of organic carbon stored by currently existing fukugi trees in the homesteads was approximately 670 ton inside a hamlet and approximately 6738 t-CO 2 in the total ten surveyed sites.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon storage of large-scale forests at both the global [5,6] and national [7][8][9] levels has gained intensive attention and is relatively well documented. In contrast, carbon storage in small-scale stands of forests has limited studies, except in few cases, e.g., forest patches in agricultural landscapes [10], agroforestry [11][12][13], and home gardens [14].…”
Section: Introductionmentioning
confidence: 99%
“…In majority of the studies, below-ground carbon stock was calculated as 15% of above-ground carbon stock (Miah, Uddin, Bhuiyan, Koike, & Shin, 2009;Ullah & Al-Amin, 2012), but in another study, it was found 14% in real field (Rahman et al, 2015) which added further errors into the estimates. In addition, confusion compounded when someone used 0.50 (Dey et al, 2014;Islam, 2013;Shin et al, 2007) as the carbon conversion factor from biomass and some other used 0.58 (Akter, Rahman, & Al-Amin, 2013;Sohel et al, 2015). Similarly, Rahman et al (2013)…”
Section: Forest Areas Covered: Spatial Distribution Of Existing Studiesmentioning
confidence: 99%
“…There are reports where herb, shrub, trees, and grass species were included in total carbon estimation (Ullah & Al-Amin, 2012). Some researchers estimated the carbon stock solely based on DBH (Dey et al, 2014;Hossain et al, 2016a), while few one considered 10-12 parameters (Rahman, 2004). Mizanur et al (2015) found that dominant mangrove species are the key indicator of ecosystem carbon stock.…”
Section: Variables Consideredmentioning
confidence: 99%